Severe aortic insufficiency‐induced cardiogenic shock treated with left atrial VA‐ECMO and emergent valve‐in‐valve TAVR - Hafez Golzarian; Arielle Thiel; Gerri Hempfling; Michael Otto; Todd Otto; Emily Shappell; Lisa Racer; Denise Martz; Christine M. Recker‐Herman; Amanda Laird; William C. Cole; John Sirak; et al. (ESC Heart Failure, 2023)
Abstract Conventional venoarterial extracorporeal membrane oxygenation (VA‐ECMO) places a functional afterload burden on the left ventricle. In the setting of acute severe aortic insufficiency‐induced cardiogenic shock, the utility of VA‐ECMO in combination with a failing valve may result in catastrophic haemodynamic consequences. This challenge is compounded when the culprit is a failing surgical bioprosthetic valve. We present a case of severe rapid‐onset bioprosthetic aortic insufficiency‐induced cardiogenic shock successfully resuscitated with left atrial VA‐ECMO promptly followed by emergent percutaneous valve‐in‐valve transaortic valve replacement. We discuss the logistics, implications, and associated haemodynamic manifestations in utilizing this strategy for such disease processes.